Proteomic and Genomic Methylation Signatures of Idiopathic Subglottic Stenosis. (3rd July 2020) - Schoeff, Stephen S.; Shi, Xudong; Young, William G.; Whited, Chad W.; Soni, Resha S.; Liu, Peng; Ong, Irene M.; Dailey, Seth H.; Welham, Nathan V.
Abstract : Objective: Idiopathic subglottic stenosis (iSGS) is a chronic inflammatory condition that causes dyspnea and affects middle‐aged women of White race and non‐Latino or Hispanic ethnicity. To better characterize its phenotype and pathogenesis, we assessed the proteomic and genomic methylation signatures of subglottic tissue collected from iSGS patients compared to controls. Study Design: Molecular analysis of clinical biospecimens. Methods: We collected subglottic tissue biopsies from 12 patients during direct laryngoscopy, immediately prior to surgical treatment of iSGS; as well as from 4 age‐, sex‐, and race/ethnicity‐matched control patients undergoing other direct laryngoscopic procedures. We isolated protein and genomic DNA, acquired proteomic data using label‐free quantitative mass spectrometry techniques, and acquired genome‐wide methylation data using bisulfite conversion and a microarray platform. We compared molecular profiles across the iSGS and control groups, and with respect to clinical course in the iSGS group. Eight of the 12 iSGS patients underwent subsequent blood collection and plasma isolation for further assessment. Results: Proteomic analysis revealed 42 differentially abundant proteins in the iSGS biopsies compared to controls, inferring enrichment of biological pathways associated with early wound healing, innate immunity, matrix remodeling, and metabolism. Proteome‐based hierarchical clustering organized patients into two iSGS and one control subgroups. Methylation analysis revealed five hypermethylated genes in the iSGS biopsies compared to controls, including the biotin recycling enzyme biotinidase ( BTD ). Follow‐up analysis showed elevated plasma BTD activity in iSGS patients compared to both controls and published normative data. Conclusion: iSGS exhibits distinct proteomic and genomic methylation signatures. These signatures expand current understanding of the iSGS phenotype, support the possibility of disease subgroups, and should inform the direction of future experimental studies. Level of Evidence: Not applicable Laryngoscope, 131:E540–E546, 2021